2009
DOI: 10.1016/j.mod.2008.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Control of Dead end localization and activity – Implications for the function of the protein in antagonizing miRNA function

Abstract: Dead end (dnd) is a vertebrate-specific component of the germ plasm and germ-cell granules that is crucial for germ-cell development in zebrafish and mouse. Dnd counteracts the inhibitory function of miRNAs, thereby facilitating the expression of proteins such as Nanos and Tdrd7 in the germ cells. Here, we show that cis-acting elements within dnd mRNA and the RNA recognition motive (RRM) of the protein are essential for targeting protein expression to the germ cells and to the perinuclear granules, respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
53
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 36 publications
3
53
1
Order By: Relevance
“…It contains a conserved RRM motif and five other motifs. As reported previously, the N-terminal RRM motif is essential for accurate localization of perinuclear germ granules, and the C-terminal amino acids contain ATPase activity that is crucial for PGC survival (Slanchev et al, 2009;Liu and Collodi, 2010). Phylogenetic analyses based on Dnd amino acid sequences revealed that vertebrates Dnd cluster into two clades, in which all examined fish species form a distinct group, whereas other vertebrates cluster in another one, and gibel carp has the closest phylogenetic relationship with crucian carp and zebrafish (Fig.…”
Section: Discussionsupporting
confidence: 63%
“…It contains a conserved RRM motif and five other motifs. As reported previously, the N-terminal RRM motif is essential for accurate localization of perinuclear germ granules, and the C-terminal amino acids contain ATPase activity that is crucial for PGC survival (Slanchev et al, 2009;Liu and Collodi, 2010). Phylogenetic analyses based on Dnd amino acid sequences revealed that vertebrates Dnd cluster into two clades, in which all examined fish species form a distinct group, whereas other vertebrates cluster in another one, and gibel carp has the closest phylogenetic relationship with crucian carp and zebrafish (Fig.…”
Section: Discussionsupporting
confidence: 63%
“…In addition, zebrafish Dnd ATPase plays a role in protecting nanos1 and TDRD7 transcripts (Liu and Collodi, 2010). In previous studies, injection of GFP-dnd 3′ UTR showed zebrafish PGCs to specifically express GFP, but zebrafish dnd 3′ UTR was shown to lack a miR-430 binding sequence (GCACUUU), which suggested that the mechanisms were independent of miR-430 regulation (Mishima et al, 2006;Slanchev et al, 2009). However, unlike zebrafish dnd, Asdnd 3′ UTR was found to contain a putative miR-430 binding site (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that dnd is exclusively expressed in PGCs during embryogenesis, and its 3′-untranslated region (UTR) could play a role in directing PGC-specific expression of the protein (Slanchev et al, 2009). In zebrafish, PGCs could be visualized by injecting artificial mRNA constructed by fusing zebrafish nanos3 3′ UTR with a green fluorescent protein (GFP) sequence, namely GFP-nos3 3′ UTR (Koprunner et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Dnd1 encodes an RNAbinding protein that controls access of specific microRNAs to their mRNA targets in testicular cancer cell lines (64) and also transports mRNAs from the nucleus to perinuclear RNA granules under stress conditions (65). We reasoned that sequence similarity between Dnd1 and A1cf, which is the RNA-binding subunit of the APOBEC1 RNA-editing complex (37,38), raised the possibility that Dnd1 acts in a similar manner with Apobec1 and therefore that Apobec1 also might control TGCT risk and transgenerational effects, either alone or in combination with Dnd1.…”
Section: Discussionmentioning
confidence: 99%